Implementation of Legal Protection (Study of Decision Number: 5/Pid.Sus/2024/PN.Kng) for Children Who Are Sexually Abused - Intan Cahyani, Mareta; Agustinus Sibarani, Frandes Surya; Muhammad Faishal, Adli; Ismayana, Ismayana; Waluyadi, Waluyadi (Jurnal Legisci, 2024)
The goal of this research is to outline the criminal penalties for those who engage in sexual activity with minors in terms of victim protection. The normative approach method is used in this investigation. Secondary data is used. Documents and literature are examined to implement data collection procedures. In the meantime, the analysis is descriptive and employs qualitative analysis. The study's findings indicated that the criminal penalties meted out to those who engage in sexual activity with minors do not fairly compensate for the victims' protection.